2009
DOI: 10.1158/1055-9965.epi-08-0817
|View full text |Cite
|
Sign up to set email alerts
|

Racial Variation in Sex Steroid Hormones and the Insulin-Like Growth Factor Axis in Umbilical Cord Blood of Male Neonates

Abstract: Background: To address whether umbilical cord blood concentrations of sex steroid hormones and the insulinlike growth factor (IGF) axis differ between AfricanAmerican and White male neonates. Methods: In 2004 and 2005, venous cord blood samples were collected from 75 African-American and 38 White male full-term uncomplicated births along with birth weight, placental weight, mother's age and parity, and time of birth. Testosterone, androstanediol glucuronide, estradiol, and sex hormone binding globulin (SHBG) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
34
2
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 42 publications
5
34
2
1
Order By: Relevance
“…Although previous studies have shown racial/ethnic differences in sex hormones (33)(34)(35), and that socioeconomic factors were more strongly associated with perceived stress in white men than in other racial/ethnic groups (36), we found no significant differences with respect to race/ ethnicity.…”
Section: Discussioncontrasting
confidence: 99%
“…Although previous studies have shown racial/ethnic differences in sex hormones (33)(34)(35), and that socioeconomic factors were more strongly associated with perceived stress in white men than in other racial/ethnic groups (36), we found no significant differences with respect to race/ ethnicity.…”
Section: Discussioncontrasting
confidence: 99%
“…2527 Moreover, pregnant African-American women have higher serum T levels, with a greater frequency of low-birth-weight babies. 2830 Experimental studies show that increasing T levels in pregnant rats to concentrations similar to levels in preeclamptic pregnancies leads to fetal growth restriction. 31;32 Furthermore, these low-birth-weight T offspring develop cardiovascular dysfunction in a sex-specific manner that is more pronounced in males than females.…”
Section: Introductionmentioning
confidence: 99%
“…Additional studies have indirectly addressed the influence of the in utero environment on the prostate cancer racial disparity. For example, we previously reported slightly higher concentrations of testosterone, estradiol [16], and leptin [17] and slightly lower concentrations of insulin-like growth factors [16] and vitamin D [18] in the cord blood of black male neonates compared with white male neonates. In addition, higher testosterone and androstenedione concentrations in black compared to white mothers have been previously reported at the beginning of gestation [19, 20] or at time of delivery [21].…”
Section: Introductionmentioning
confidence: 99%